ANALYSIS OF THE EFFECT OF ACCOUNTING EARNINGS AND OPERATING CASH FLOW TO STOCK RETURN MANUFACTURING COMPANIES LISTED ON STOCK EXCHANGES IN INDONESIA (Students' Journal of Accounting and Banking, 2012)
The financial report is a major source of financial information that is essential for a number of users or investors in making economic decisions. The importance of the financial statements as a source of information for investors, raises the interest to examine the information in the financial statements in particular accounting earnings and operating cash flow are reflected in stock returns.The problem in this study is how the Accounting Profit, Operating Cash Flow to stock return on manufacturing companies in Indonesia Stock Exchange (IDX). While the purpose of the study is to examine and analyze the effect of accounting earnings, operating cash flow to stock return on manufacturing companies in Indonesia Stock Exchange (IDX).The population in this study is a manufacturing company listed on the Indonesia Stock Exchange as many as 54 companies. Sample was determined by purposive sampling technique in order to obtain a representative sample in accordance with the specified criteria. The sample in this study was 162 manufacturing companies. The variable in this study is twofold; independent variables include Accounting Earnings and Operating Cash Flow. As for the dependent variable is the stock return in the manufacturing companies listed on the Stock Exchange.The results of the analysis has been done, it can be seen that the Profit Accounting and Operating Cash Flow has a positive and significant impact on stock returns, which means higher accounting earnings and operating cash flow, the greater the benefit you'll get from ownership of shares (stock returns).Keywords: Accounting Profit, Operating Cash Flow and Stock Return